2010
DOI: 10.1016/j.jaci.2009.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of outdoor versus indoor fungal spores on asthma morbidity in inner-city children

Abstract: Background While sensitization to fungal allergens is prevalent in inner-city children with asthma, the relationship between fungal exposure and morbidity is poorly understood. Objective We examined relationships between fungal sensitization, exposure and asthma morbidity in inner-city children. Methods Participants were 5–11 years old and enrolled in the Inner-City Asthma Study. This report includes the subset of children with at least 1 positive skin test to a fungal allergen extract; for these children,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(93 citation statements)
references
References 33 publications
(42 reference statements)
1
88
0
4
Order By: Relevance
“…The relationships among allergic exposure, the fungal presence in indoor and outdoor environments and consequent allergic diseases are not fully understood 5,6 . Therefore, it is important to know both the frequency of certain airborne fungi and their distributions according to the season and the main environment (i.e., indoor or outdoor) in order to evaluate their correlations with respiratory symptoms related to allergic processes [7][8][9] .…”
mentioning
confidence: 99%
“…The relationships among allergic exposure, the fungal presence in indoor and outdoor environments and consequent allergic diseases are not fully understood 5,6 . Therefore, it is important to know both the frequency of certain airborne fungi and their distributions according to the season and the main environment (i.e., indoor or outdoor) in order to evaluate their correlations with respiratory symptoms related to allergic processes [7][8][9] .…”
mentioning
confidence: 99%
“…51 The prevalence of mold sensitization in children with persistent asthma is approximately 50%, and the most common species to which children are sensitized and exposed are Alternaria, Aspergillus, Cladosporium, and Penicillium. 52 Although Alternaria and Aspergillus are derived from outdoor sources, they are present indoors and may be clinically relevant. 53 The National Survey of Lead and Allergens in Housing found that 56% of homes had levels of some molds above thresholds observed to be associated with asthma symptoms.…”
Section: Dampness and Moldmentioning
confidence: 99%
“…54 Children sensitized and exposed to the major indoor molds appear to be at greater risk of asthma exacerbations. 52 Remediation of mold has been shown to reduce symptoms and medication use in several populations, and its effects may not depend on whether the population is sensitized to mold. 55,56 The evaluation of a patient with persistent asthma includes an assessment of sensitization to the major indoor molds, which can be accomplished with specific IgE testing performed on a blood sample or through referral to a board-certified allergist for skin testing.…”
Section: Dampness and Moldmentioning
confidence: 99%
“…al. 2010), with the latter outcome also having dose-response associations with total indoor fungi (Pongracic et. al.…”
Section: Exposure Metricmentioning
confidence: 99%